Peasant mobilization, nation and democracy - López, Sinesio (1989)
One of the most outstanding features of Peruvian politics in recent decades is the vigorous presence of the popular classes in the national political scene. Before 1930, the people were practically absent not only from the spaces of the great political decisions but also from the great social scene. Not only did it fail to establish itself as an organized force with its own political project, but it was also unable to centralize its forces to assert its immediate demands and interests.